Effect of selected ammonia escape inhibitors on carbon dioxide capture and utilization via calcium carbonate precipitation. Issue 42 (December 2020) - Czaplicka, Natalia; Konopacka-Łyskawa, Donata; Kościelska, Barbara; Łapiński, Marcin
Graphical abstract: Highlights: Carbon dioxide sequestration was carried out in calcium chloride solutions. Ammonia was used as a CO2 absorption promoter. Organic and inorganic inhibitors of NH3 escape were added to the reaction mixture. The efficiency of CO2 sequestration was the highest in the presence of glycerol. Abstract: Carbon dioxide was used to precipitate CaCO3 with CaCl2 solution in the presence of NH3 as a CO2 absorption promoter. Compounds that were previously indicated as inhibitors of ammonia escape during CO2 absorption were also added to the reaction mixture. Inorganic salts, i.e. ZnCl2, CuCl2, CoCl2, and organic substances, i.e. glycerol, ethylene glycol and triethanolamine were tested inhibitors in this work. A model post-distillation liquid from the Solvay process was used as the reaction mixture, while the gas stream fed into the system had a composition corresponding to the exhausted gases produced by the fossil fuels combustion. The purpose of this research was to investigate the efficiency of CO2 sequestration and the consumption of calcium ions during precipitation in the carbonation processes and determine the characteristics of produced CaCO3 particles. Of the tested additives, glycerol turned out to be the most effective, because its presence resulted in increased calcium ion consumption and CO2 sequestration compared to the control process. 90.5 % CO2 sequestration and 88.1 % Ca 2+ consumption were obtained. The CaCO3 particles obtained in the presence of all tested organic inhibitors were in the form of vaterite and were characterized by a significantly larger specific surface area and larger pore volume.